7a-3=3+6n

Simple and best practice solution for 7a-3=3+6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a-3=3+6n equation:


Simplifying
7a + -3 = 3 + 6n

Reorder the terms:
-3 + 7a = 3 + 6n

Solving
-3 + 7a = 3 + 6n

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 7a = 3 + 3 + 6n

Combine like terms: -3 + 3 = 0
0 + 7a = 3 + 3 + 6n
7a = 3 + 3 + 6n

Combine like terms: 3 + 3 = 6
7a = 6 + 6n

Divide each side by '7'.
a = 0.8571428571 + 0.8571428571n

Simplifying
a = 0.8571428571 + 0.8571428571n

See similar equations:

| 30=5(x+2) | | 0.98(8)+1.04p=0.98(8+p) | | 3(2x-1)-3=48 | | 2(x-1)=-x+16 | | -x-9=3x+11 | | -x+47=4(x-2) | | -7x-3x+2=-8 | | 2x^2+4y^2-4x-24y+36=0 | | (2x-3)/7=(3x)/7-2x | | p^3-4p^2-p+4= | | 2.2q-3.9-2.8q=-1.6q-1.8 | | 4n=m(5-n) | | 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 | | 5.5q-4.6-6.6q=2.2-1.1q-2.4 | | 6.1x+3=5.1x | | 10(-2x+1)=-12(x+2)+34-8x | | 7x+9-8x+4=6x-7x-5 |

Equations solver categories